Experience with hookwire localisation excision biopsy at a medical centre in Malaysia - Ng, C.H.; Lee, K.T.; Taib, N.A.; Yip, C.H. (2010)
Introduction: With an increasing number of women undergoing breast screening, an effective method of removing non-palpable lumps detected by mammography or sonography is by hookwire localisation excision biopsy (HWLB). The aim of this paper was to audit the practice of HWLB at the University Malaya Medical Centre. Methods: Patients with benign or suspicious preoperative diagnoses of a non-palpable lump and who underwent HWLB were included in this study. Pathological examination of the surgical specimens was conducted and a correlation with preoperative assessment modalities was reported. Results: A total of 59 HWLBs were carried out in 57 female patients. The mean age of the patients was 51.5 years. The overall malignancy rate was 32.3 percent (19 out of 59 cases) with a benign to malignant ratio of 3.1 to 1. Ten of these cases were ductal carcinoma-in-situ. Out of 25 patients who were suspicious on preoperative assessment, 16 malignancies were found, while in the 33 patients thought to be benign on preoperative assessment, there were three malignancies, giving a sensitivity of 84.2 percent and a specificity of 76.9 percent (p is less than 0.05). The mean tissue volume excised in 53 available records was 50.0 cm(3), with pathological tissue comprising only 15.4 percent of the total excised volume. Clear margins were obtained in 42.1 percent of the patients. The overall operative complication rate was 10.2 percent. Conclusion: Malignancy was reported in one third of women undergoing HWLB, of which 16 had suspicious features on radiological assessment and/or fine needle aspiration cytology/core needle biopsy preoperatively. Non-palpable lumps should be excised by HWLB for a definitive diagnosis in case of any suspicion on preoperative assessment, as the prognosis is excellent.